The IMF and Argentina, 1991-2001 - Mateos y Lago, Isabelle (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2004)
This report evaluates the role of the IMF in Argentina during 1991-2001, focusing particularly on the period of crisis management from 2000 until early 2002. The primary purpose of the evaluation is to draw lessons for the IMF in its future operational work. The evaluation suggests ten lessons, in the areas of surveillance and program design, crisis management, and the decision-making process, and, on the basis of these lessons, offers six sets of recommendations to improve the effectiveness of IMF policies and procedures.